Development of A Prototype of the M-Health_Desila Application (Digital Elderly Self-Health Screening Application) for Early Screening of Degenerative Diseases in the Elderly - Dewi Erna Marisa; Endah Sari Purbaningsih; Hendri Rosmawan; Fitri Nurhadits (Indonesian Journal of Global Health Research, 2026)
Degenerative diseases in the elderly, such as hypertension, diabetes, and osteoarthritis, are major health issues in Indonesia. Early screening is often suboptimal due to limited healthcare access, low health literacy, and the absence of elderly-friendly digital media. This study aimed to develop M-Health_Desila prototype application to support early screening of degenerative diseases in the elderly. This study employed a research and development design comprising a literature review, needs analysis, system design, prototype development, expert validation, and limited trials. Expert validation was conducted by health and technology specialists, while the limited trials involved 10 health cadres and 10 elderly participants in Cirebon. The prototype was successfully developed with features including digital questionnaires, health history, automated screening results, and follow-up recommendations. Validation confirmed content suitability with suggestions to improve icons and add audio features. Limited trials showed cadres rated the app as very feasible (60%) and feasible (40%), while elderly participants rated it feasible (50%), very feasible (30%), and moderately feasible (20%). Technology readiness level increased from 2 to 3. The m-health application is considered feasible for early screening of degenerative diseases in the elderly, though further interface improvements are needed to enhance usability.